Rethinking Value Management (VM) Integration within the Strategic Phase of Construction Project Value Chain - Ab Ghani, Rohanis; Zakaria, Norhanim; Mei Ye, Kho (International Journal of Sustainable Construction Engineering and Technology, 2022)
This is an attempt of rethinking Value Management (VM) integration within the strategic phase of the Malaysian public construction project value chain. Currently, such strategic VM integration is not evidenced by any value study. The earliest existing VM study intervention, namely Value Assessment (VA), only takes place after the Government approves the project budget. The budget approval activity demarcates that the project has reached the ‘decision to construct’ point at the end of the strategic phase. This indicates a vacuum of VM integration within the strategic phase of the project value chain. This conceptual study is conducted through retrieving literature review and obtaining consultation from VM experts in the public sector. First, the study has verified the vacuum of VM integration within the strategic phase of the Malaysian public construction project value chain. Secondly, in responding to the vacuum, this study identifies the opportunity of integrating VM within the strategic phase. Ultimately, two (2) opportune VM study interventions within the strategic phase are determined. This finding describes the value studies’ characteristics in terms of the study timings, main study objectives and the issues addressed by the respective VM study interventions.